FAKTOR KOMUNIKASI YANG MEMPENGARUHI ADOPSI PROGRAM IMUNISASI DI KOTA SERANG - Fajarwati, Noerma Kurnia; Laksana, April (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
This research is motivated by the spread of diphtheria outbreaks caused by the existence of an immunity gap due to the low level of immunization in the people of Serang City. The purpose of this study was to determine the effect of recipient characteristics, innovation characteristics and communication sources both partially and simultaneously on the level of immunization program adoption. This research is based on the theory of innovation diffusion to explain the community's decision to adopt an immunization program. The study population was residents of the Curug Subdistrict of Serang City who had children aged 0 to 18 months and had included their children with immunizations. The number of samples was determined as many as 125 respondents selected by snowball sampling technique. The research data were analyzed using the SPSS version 20.00 program with multiple linear regression methods. Based on the hypothesis test results obtained 1) Characteristics of recipients proved to have a positive effect on the adoption of the immunization program in Serang City. 2) The characteristics of innovation proved to have a positive effect on the adoption of the immunization program in Serang City. 3) The source of communication proved to have a positive effect on the adoption of the immunization program in Serang City. The magnitude of the effect of recipient characteristics, innovation characteristics and communication sources on the adoption of the immunization program is shown by a coefficient of determination of 93.7%